Uterine Fibroids. What We Know and What We Need to Know (Global Journal of Medical Research, 2022)
Uterine fibroids (UFs) are the most common tumours of the female reproductive system and represent a significant health issue worldwide. UFs develop during reproductive span and often shrink after menopause. UFs affect over 70% of women by the onset of menopause. Uterine fibroids arise from myometrial smooth muscle cells. UFs can be solitary or multiply and their size varies from microscopic to giant. Nowadays the exact cause of UFs remains unknown, but it is assumed that genetic abberations along with steroid hormones and growth factors play a pivotal role in the tumour development. In most cases UFs are asymptomatic and therefore it is difficult to estimate their actual prevalence. Symptomatic UFs present with abnormal menstrual bleeding, pelvic and low back pain, bulk symptoms, infertility and have a strong impact on health-related-quality-of-life (HRQL). Early diagnosis and treatment of UFs as well as preventive measures, especially for patients from high-risk groups, should be a priority. This article presents current data about pathophysiology, diagnosis and management of UFs.
Keywords: leiomyoma; myometrium; estrogens; progesterone; growth factors; menopause; fertility; uterine myomectomy; hysterectomy